2021
DOI: 10.1016/j.ejca.2020.11.015
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infections in melanoma patients treated with PD-1 inhibitors: A survey of the German ADOREG melanoma registry

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 9 publications
0
25
0
2
Order By: Relevance
“…Among these, one study about coronavirus, three surveys and 21 researches that included less than four patients were excluded after full text review. Finally, 13 studies reported ICI use in cancer patients and prognosis of COVID-19 infection [8,[18][19][20][21][22][23][24][25][26][27][28][29]. The 13 articles consisted of ten cohort studies and three case series and were included for the meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among these, one study about coronavirus, three surveys and 21 researches that included less than four patients were excluded after full text review. Finally, 13 studies reported ICI use in cancer patients and prognosis of COVID-19 infection [8,[18][19][20][21][22][23][24][25][26][27][28][29]. The 13 articles consisted of ten cohort studies and three case series and were included for the meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…Of these 13 studies, clinical outcomes were defined as hospitalization in five studies, severity in eight studies and mortality in 11 studies (Table 1). However, there was nonuniformity in the criterion of the time interval from last dose to COVID-19 diagnosis (Table 1) [8,18,19,21,[23][24][25].…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, patients receiving anti-PD-1 within 6 weeks prior to COVID-19 diagnosis tend to develop less severe disease compared with patients receiving anti-PD-1 within to 6 months prior to diagnosis. In addition, severe disease was found in only 2 of 13 patients with melanoma treated with anti-PD-1 antibody alone or in combination with CTLA4 blockade therapy within 0 to 51 days prior to SARS-CoV-2-positive test (10). The evidence to date suggests that SARS-CoV-2 infection does not enhance immune-related toxicities associated with PD-1 and CTLA4 blockade immunotherapies when administered prior to infection.…”
mentioning
confidence: 99%